DEVELOPMENT OF MERAH-PUTIH CATALYST FOR FCC UNIT - Anthony, Derrick
The demand for motor vehicle fuel in Indonesia increases annually, making it crucial to boost fuel production for self-sufficiency. The FCC unit is essential for cracking heavy fractions into lighter, usable fuel. A key factor in this process is the FCC catalyst, which Indonesia currently cannot produce independently. FCC catalysts typically consist of Y zeolite, matrix, binder, and additives. This study aims to find the optimal FCC catalyst composition by varying the amounts of its components: HY zeolite, metakaolin (matrix), silicon oxide (binder), and ZSM-5 (additive). HY zeolite was synthesized and characterized using X-ray diffraction and surface area analysis, achieving 46.9% crystallinity and a surface area of 752.6 m²/g. Catalyst activity tests were conducted using the microactivity test (MAT) with Vacuum Gas Oil (VGO) feed to produce liquid and gas products. The highest liquid yield came from FCC-4420, reaching 51% of the total catalyst product, with a gasoline composition of 97.8%. The highest gas yield was obtained from FCC-3421, reaching 66.8% with a composition of 67.3%. This research identifies optimal catalyst compositions to improve Indonesia’s fuel production capabilities.